Does corporate tax avoidance promote managerial empire building?. Issue 1 (April 2022) - Shams, Syed; Bose, Sudipta; Gunasekarage, Abeyratna
Abstract: We examine the association between corporate tax avoidance and empire building using 35, 060 firm-year observations from the United States (US) for the period 1991–2015. We build a composite empire building measure by conducting a factor analysis on four popular empire building proxies used in the literature. We find a positive association between this composite measure and the four proxies used to represent the tax avoidance of firms in our sample. As our results suggest, agency problems are inflicted upon firms employing tax avoidance strategies which, in turn, facilitate managerial rent extraction through aggressiveness in growth and the accumulation of assets. Furthermore, the relationship of corporate tax avoidance to managerial empire building is found to be more pronounced in firms with weak governance, poor monitoring mechanisms, greater Chief Executive Officer (CEO) power and weak corporate social responsibility (CSR) performance. We also find that empire building-motivated tax avoidance leads to lower firm valuation. Our results remain insensitive even when employing several robustness tests.